ANALISIS PENGARUH TALENT MANAGEMENT, EMPLOYEE RETENTION DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KINERJA KARYAWAN - Rasyid, Rendy Zulfan Maulana; M. Abdi Dzil Ikhram (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
The objective of this research is to measure the effects of talent management, employee retention, and perceived organizational support on the performance of employees a Dialogi Café. The data of this quantitative explanatory research was harvested from questionnaires distributed to 57 permanent employees of Dialogi Café from three stores: Dialogi Space and Coffee, Dialogi Signature, and Dialogi Coffee and Bistro. This study uses saturated sampling since the entire population were used as the sample. Here descriptive analysis and Structural Equation Modelling – Partial Leas Squares were performed in SmartPLS v.3.3.9. This study finds that the talent management and the employee retention do not significantly influence employee performance and that perceived organizational support significantly affects employee performance.